Unveiling the Competence of BTLED and BTVTED Teachers Teaching Trainer’s Methodology II Across Mindanao, Philippines - Nolie C Guadalquiver Jr; Ariel C Balio Jr (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to assess the competence of BTLED and BTVTED teachers teaching Trainer’s Methodology II across Mindanao, identifying their skills, challenges, and strategies while proposing reforms to enhance teacher capability, certification accessibility, and curriculum alignment with TESDA and industry standards. Methodology: An Explanatory Sequential Mixed-Method design was used, utilizing a validated survey questionnaire via Google Forms and in-depth interviews. Data were analyzed using both quantitative and qualitative approaches supported by SPSS 26.0. The study employed Vygotsky’s Constructivist Learning Theory and Anderson’s ACT-R Theory to frame data interpretation and analysis across selected Mindanao SUCs and LUCs. Main Findings: Results showed that most BTLED and BTVTED teachers are young professionals facing outdated TESDA modules, limited access to Trainer’s Methodology II assessment centers, and inadequate institutional support. Despite challenges, teachers exhibit adaptability through contextualized, project-based, and problem-based learning strategies. Peer mentoring and technology integration improve teaching effectiveness. However, excessive administrative workload, certification barriers, and unequal resource distribution hinder competence development. The study highlights the need for decentralized certification, updated training modules, and enhanced teacher support systems. Novelty/Originality of this study: This study is the first regional analysis of BTLED and BTVTED teacher competence in Trainer’s Methodology II across Mindanao. It introduces an evidence-based framework integrating social constructivism and cognitive automation to address gaps in certification and curriculum alignment. Its localized recommendations advance teacher training policy and technical-vocational education standards in Philippine higher education.